2009
DOI: 10.1002/bem.20554
|View full text |Cite
|
Sign up to set email alerts
|

Signal transduction of the melatonin receptor MT1 is disrupted in breast cancer cells by electromagnetic fields

Abstract: The growth of estrogen-receptor positive breast cancer cells is inhibited by the pineal gland hormone, melatonin. Concern has been raised that power-line frequency and microwave electromagnetic fields (EMFs) could reduce the efficiency of melatonin on breast cancer cells. In this study we investigated the impact of EMFs on the signal transduction of the high-affinity receptor MT1 in parental MCF-7 cells and MCF-7 cells transfected with the MT1 gene. The binding of the cAMP-responsive element binding (CREB) pro… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
14
0

Year Published

2010
2010
2017
2017

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 19 publications
(14 citation statements)
references
References 23 publications
0
14
0
Order By: Relevance
“…As a matter of fact, the in vitro response to ELF fields has been shown to be modulated by a variety of physical and/ or biological parameters that could potentiate or inhibit the cellular sensitivity to MF. These parameters include the field strength, the wave form, the exposure cycle and duration, the genetic characteristics of the cells (66), the presence of pharmacological drugs or endogenous hormones like melatonin (19,67) or the redox status of the system (68). Pirozzoli et al (69) reported a significant increase (10%; p≤0.05) in proliferation of the human neuroblastoma cell line LAN-5, after 7 days of continuous exposure to 50 Hz, 1 mT MF.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…As a matter of fact, the in vitro response to ELF fields has been shown to be modulated by a variety of physical and/ or biological parameters that could potentiate or inhibit the cellular sensitivity to MF. These parameters include the field strength, the wave form, the exposure cycle and duration, the genetic characteristics of the cells (66), the presence of pharmacological drugs or endogenous hormones like melatonin (19,67) or the redox status of the system (68). Pirozzoli et al (69) reported a significant increase (10%; p≤0.05) in proliferation of the human neuroblastoma cell line LAN-5, after 7 days of continuous exposure to 50 Hz, 1 mT MF.…”
Section: Discussionmentioning
confidence: 99%
“…In order to identify and characterize the cellular processes involved in the potential proliferative effects of ELF MF, a number of studies have investigated the in vitro response to those fields when administered in combination with different chemical species including antioxidants like melatonin or tamoxifen (14)(15)(16)(17)(18)(19), or radical-inducing agents like menadione (20) and tumor promoters like DMBA (21).…”
Section: Introductionmentioning
confidence: 99%
“…However, it also acts as a natural free radical antioxidant scavenger. This would explain its beneficial effect in reducing EMF-induced damage in breast cancer model [83] and its neuroprotective rescue after RF oxidative stress induction in neuron primary culture [84]. Interestingly, melatonin has been reported to play a relevant role in regulation of human newborn protection in enhanced environmental oxidative stress (OS) present at time of birth.…”
Section: The Effect Of Rf Exposure In Vivo: New Insights On Biosystemmentioning
confidence: 99%
“…Some tentative studies proposed that EMF affected melatonin production in the same way as light in the evening. A suppressive effect of melatonin on estrogen receptor positive breast cancer was found and supported by recent experiments in vitro (Hill et al, 1988;Girgert et al, 2008;Girgert et al, 2010), and researchers indicated that melatonin acted as a potent antioxidant or a protective factor in the immune system (Guerrero et al, 1992;Reiter et al, 1995). Though the relationship between melatonin and breast cancer development had been confirmed in vivo and in vitro experiments, it failed in prospective epidemiological studies (Travis et al, 2004).…”
Section: Discussionmentioning
confidence: 91%